The Development of Instrument of Reading Literacy Assessment on Indonesian Language Learning in Quality Medan University - Yohana Yohana; Mutsyuhito Solin; Wisman Hadi (BIRCU, 2019)
This study is aimed to describe the development of instrument of reading literacy assessment on Indonesian language learning in Quality Medan University. The assessment instrument which is developed in the form of a guidebook of reading literacy on the PISA reference which is used as a handbook for lecturers in the field of learning studies reading texts. The population of this study is the first semester students of the Medan Quality Private University. The authors took a sample of 30 students. The result shows that the development of reading literacy assessment instrument on the PISA reference, is a direct assessment because students immediately show evidence of mastery of competencies when the assessment is conducted. The use of reading literacy assessment increases the results of high-level understanding of students, this is indicated by the results of student scores after using the reading literacy assessment on the PISA reference was 2283 compared to the results before 1364.